Impact of rewards on retention of workers: a study of operative level employees in the apparel industry - Weerasinghe, T.D.; Batagoda, C.K.; Nadeera, M.G.N.L. (University of Jaffna, 2012)
The purpose of this study was to investigate the impact of rewards on employee retention and to construct a model which could be used to predict the retention intention of operative level employees in apparel industry. This was carried out as a cross sectional field study among a sample of 320 operative level employees in the apparel industry. Convenience sampling was applied to select the sample and the investigation was done in three leading garment factories in the industry. A self administered pre tested questionnaire was used to collect data which was met the accepted standards of validity and reliability. Correlation test was used to analyse data with the stepwise regression analysis to fit a regression model. P–value was used to test mentioned hypotheses. It was found that basic salary, welfare and incentives significantly correlated with the retention of employees. The fitted regression model explained 67.7% variation in dependent variable where basic salary and welfare were taken as the best two predictors of retention intention in the tested domain. Basic salary was more important in predicting employee retention than the welfare as standardized coefficient of beta was greater. It could be recommended to review basic salaries and welfare facilities given for operative level workers in garment factories